Evidence of Population Declines among Common Eiders Breeding in the Belcher Islands, Northwest Territories - Robertson, Gregory J.; Gilchrist, H. Grant (ARCTIC, 1998)
Information regarding the status of common eiders, Somateria mollissima, breeding in the Canadian Arctic is sorely lacking. In 1997, we surveyed five island archipelagoes in the Belcher Islands in Hudson Bay (56 00 - 57 30 N, 79 30 - 80 00 W) from 3 to 23 July. Our results were compared with eider surveys of the same islands completed between 1985 and 1989 using a standard protocol. We found 1416 eiders on 431 islands. Most (94.1%) were found while the female was still incubating. In all five island groups surveyed, the number of nesting eiders declined significantly (overall decline of 75.0% from 1985-88 to 1997, range: 62.3-84.0%). In 1997, nesting islands and adjacent waters were free of ice, and eiders nested early and laid large clutches (range: 4.0-4.4±1.0-1.2 SD). These conditions indicate a good nesting season, and we inferred that extensive nonbreeding by female eiders in 1997 did not account for the observed decline. A large reported die-off of eiders during the winter of 1991-92, which occurred when areas of open water froze, was the most likely cause of the decline. Our results raise serious conservation concerns, because eider populations are sensitive to reductions in adult survival and this population is harvested throughout the year by subsistence hunters. On a grandement besoin d'information sur le statut de l'eider à duvet Somateria mollissima qui niche dans l'Arctique canadien. En 1997, du 3 au 23 juillet, on a effectué des relevés dans cinq archipels des îles Belcher situées dans la baie d'Hudson (56°00'-57°30' N., 79°30'-80°00' O.) On a comparé nos résultats suivant un protocole normalisé à des relevés d'eiders effectués dans les mêmes îles entre 1985 et 1989. On a trouvé 1416 eiders dans 431 îles. La plupart (94,1 p. cent) ont été relevés alors que la femelle était encore en train de couver. Dans chacun des cinq groupes d'îles étudiés, le nombre d'eiders nicheurs avait enregistré une baisse importante (déclin global de 75,0 p. cent de 1985 à 1989, fourchette de 62,3 à 84,0 p. cent). En ...